Analisis Ekonomi dan Finansial pada Proyek Kereta Cepat Jakarta - Bandung - Widyasti, Rinanda Putri; Purba, Aleksander; Karami, Muhammad (Universitas Lampung, 2018)
This study aims to analyze the economic and financial viability of the Jakarta - Bandung high-speed railway using three scenarios, the best scenario, the medium scenario, and the worst scenario. Where the three scenarios are using 75% load factor with discount factor level of 2% and 3,46%. A project is considered feasible by comparing feasibility parameters, such as NPV, BCR, PI, EIRR / FIRR, and payback period. Based on the results obtained on the feasibility parameters used, showing the economic and financial feasibility analysis with the discount rate of 2% and 3,46% in the best, medium and worst scenario, the project is declared eligible to be built, due to the eligibility of economic feasibility. Keywords:High-speed, economic feasibility, financial feasibility, feasibility parameters